2015
DOI: 10.1007/s00540-015-1991-2
|View full text |Cite
|
Sign up to set email alerts
|

Effective method of continuous rocuronium administration based on effect-site concentrations using a pharmacokinetic/pharmacodynamic model during propofol–remifentanil anesthesia

Abstract: The results suggest that our method may be one of the most reliable protocols for the continuous administration of Rb described to date for maintaining suitable muscle relaxation during surgery without excessively prolonged effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The median rocuronium dose used is in line with previous reports. 30,31 In our study, advanced age, 12 lower BMI, and higher ASA class decreased the amount of rocuronium needed. Previous reports on the effect of BMI on rocuronium requirements are conflicting.…”
Section: Discussionsupporting
confidence: 46%
“…The median rocuronium dose used is in line with previous reports. 30,31 In our study, advanced age, 12 lower BMI, and higher ASA class decreased the amount of rocuronium needed. Previous reports on the effect of BMI on rocuronium requirements are conflicting.…”
Section: Discussionsupporting
confidence: 46%
“…Therefore, it is essential to be able to determine the optimal rates of continuous administration of Rb in accordance with the individual patient. We previously reported an effective continuous rocuronium administration method that was based on the simulated effect-site concentrations obtained from a pharmacokinetic/pharmacodynamics model during propofol anesthesia [8]. Our results showed that the simulated rocuronium concentration at the time of recovery to a first twitch (%T1) > 0% after the initial bolus administration of rocuronium was a good indicator of the optimal effect-site concentrations that would occur during continuous rocuronium administration under propofol anesthesia.…”
Section: Introductionmentioning
confidence: 90%
“…Moriyama et al [6] developed a continuous administration method for rocuronium based on data obtained after bolus administration. They calculated the effect-site concentration of rocuronium when a T1 in response to TOF stimuli appears following bolus administration (recovery concentration) under anesthesia with propofol and remifentanil using the pharmacokinetic parameters provided by Wierda et al [5].…”
mentioning
confidence: 99%